2024
DOI: 10.1002/uog.27517
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐genome sequencing analysis in fetal structural anomalies: novel phenotype–genotype discoveries

Q. Qi,
Y. Jiang,
X. Zhou
et al.

Abstract: ObjectivesThe identification of structural variants and single nucleotide variants is essential in finding molecular etiologies of monogenic genetic disorders. Whole genome sequencing (WGS) is becoming more widespread in genetic disease diagnosis. However, data on its clinical utility remain limited in prenatal practice. We aimed to expand our understanding of implementing WGS in the genetic diagnosis of fetal structural anomalies.MethodsWe employed trio WGS with a minimum coverage of 40X on the MGI DNBSEQ‐T7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…However, a recent systematic review, concluded that the incremental yield of WGS over CMA and ES is small and statistically non‐significant in the investigation of congenital malformations detected in the perinatal period or during infancy 27 . On the other hand, another recent study of 17 fetuses with aberrations detected by ultrasound showed an incremental diagnostic yield of 11.8% in WGS over CMA and ES, as WGS detected two small‐size exon‐level CNVs beyond the detection levels of CMA and ES 28 . Conducted in a clinical setting, this study focused on SNVs, INDELs and SVs that were exonic or predicted to cause splice variants.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent systematic review, concluded that the incremental yield of WGS over CMA and ES is small and statistically non‐significant in the investigation of congenital malformations detected in the perinatal period or during infancy 27 . On the other hand, another recent study of 17 fetuses with aberrations detected by ultrasound showed an incremental diagnostic yield of 11.8% in WGS over CMA and ES, as WGS detected two small‐size exon‐level CNVs beyond the detection levels of CMA and ES 28 . Conducted in a clinical setting, this study focused on SNVs, INDELs and SVs that were exonic or predicted to cause splice variants.…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that the strength of WGS lies in its comprehensiveness; in addition to its ability to detect both copy‐number variants (CNVs) and single‐nucleotide variants, removing the need for two separate analyses, WGS can offer targeted evaluation for specific repeat expansions and uniparental disomy. There is at least one study published to date that demonstrated the strength of WGS, which detected two small exonic CNVs beyond the detection thresholds of chromosomal microarray analysis and ES 2 . As chromosomal aberrations are a well‐known cause of prenatally detected congenital malformations, the diagnostic yield of WGS will increase if fetuses are not prescreened for chromosomal aberrations.…”
mentioning
confidence: 99%
“…However, we believe that the strength of WGS lies in its comprehensiveness; in addition to its ability to detect copy‐number variants (CNVs) and single‐nucleotide variants, removing the need for two separate analyses, WGS can offer targeted evaluation for specific repeat expansions and uniparental disomy. There is at least one study published to date that demonstrated the strength of WGS, which detected two small exonic CNVs beyond the detection thresholds of chromosomal microarray analysis and ES 2 . As chromosomal aberrations are a well‐known cause of prenatally detected congenital malformations, the diagnostic yield of WGS will increase if fetuses are not prescreened for chromosomal aberrations.…”
mentioning
confidence: 99%